The Week Effect of the Returns and Volatilities: The Case of the Taiwanese Stock and Option Markets - Hsieh, Tsung-Yu; Kuo, Wen-Hsiu; Lee, Huai-I (Journal of Asian Business Strategy, 2013)
In the past two decades, an increasing number of equity market anomalies have been reported in the literature, thus raising doubts about the applicability of the efficient market hypothesis and the capital asset pricing model. The Taiwan Stock Exchange Capitalization Weighted Stock Index Option (TXO) was introduced by the Taiwan Futures Exchange on December 24, 2001. Since the underlying asset of the TXO is the Taiwan Stock Exchange Capitalization Weighted Stock Index (TSI), the two instruments are highly correlated. The purpose of this paper is to investigate the week effects with regard to returns and volatilities for both the TXO and TSI. The results show that there is little evidence of the week effect for returns on the TXO, while it does exist for returns on the TXO. For call options, the lowest return appears on Thursday and the highest on Monday. For put options, the lowest return appears on Friday and the highest on Thursday. The evidence also shows that week effects also exist with regard to the volatilities on both the equity and option markets. The greatest volatility appears on Friday for both the TXO and TSI, and the lowest on Wednesday for the TSI.